Polyethyleneimine stabilized nanoscale zero-valent iron-magnetite (Fe3O4@nZVI-PEI) for the enhanced removal of arsenic from acidic aqueous solution: Performance and mechanisms. Issue 6 (December 2022) - Akoto, Justice Delali; Chai, Fei; Repo, Eveliina; Yang, Zhihui; Wang, Danyang; Zhao, Feiping; Liao, Qi; Chai, Liyuan
Abstract: Nanoscale zero-valent iron (nZVI) particles have a high removal affinity toward arsenic. However, particle agglomeration and surface passivation hinder their practical application in wastewater treatment. Herein, we report the design and synthesis of an economically viable polyethyleneimine stabilized nZVI-magnetite (Fe3 O4 @nZVI-PEI) that exhibits a fast and efficient removal of arsenic (As(III/V)) from wastewater. Microstructure analyses by SEM and TEM indicated that PEI efficiently minimized particle agglomeration. The higher the point of zero charge (pHpzc ) value of Fe3 O4 @nZVI-PEI (∼9.4) over bare Fe3 O4 @nZVI (∼8.2) is indicative of the role of PEI in the sorption of the arsenic species. The experimental results showed a removal efficiency of 95.8% for As(III) and 90.5% for As(V) at an optimum pH of 3.0. The adsorption kinetics followed the pseudo-second-order and the equilibrium isotherm data fitted to the Sips model with the superior maximum adsorption capacities of 572.40 mg/g for As(III) and 548.80 mg/g for As(V). FTIR, XRD, and XPS analyses provided insight into the possible adsorption mechanism that arsenic is taken up by generating monodentate and bidentate inner-sphere complexes with -OH, electrostatic interactions with primary amines, and partial oxidation of As(III) to As(V). In contrast to Cl -, NO3 -, and SO4 2-, PO4 3- showed a significant competitive effect on the sorption of both As(III/V) species. Overall, this work provides a practical and highly efficient approach for arsenic remediation in wastewater and contaminated soils, and simultaneously resolves the stabilization problems of nZVI nanoparticles. Graphical Abstract: The study report one concept for fabrication of polyethyleneimine stabilized nZVI-magnetite (Fe3 O4 @nZVI-PEI) serving as an efficient adsorbent for the remediation of As(III) and As(V) contaminated wastewater. The proposed material exhibits excellent removal efficiency toward both As(III) and As(V). The arsenic is taken up by generating monodentate and bidentate inner-sphere complexes with -OH, electrostatic interactions with primary amines, and partial oxidation of As(III) to As(V). ga1 Highlights: Fe3 O4 @nZVI-PEI was prepared for the efficient removal of both As(III) and As(V) from wastewater. High removal efficiencies of 95.8% for As(III) and 90.5% for As(V) were achieved at optimum pH 3.0. The adsorption was well fitted by Sips and pseudo-2nd-order models for both of As(III) and As(V). XPS, XRD, EDS, and FTIR results revealed a probable synergetic effect of adsorbent constituents.